In Silico Analysis of Centella asiatica Phytochemicals Targeting the KEAP1–NRF2 Pathway as Potential Radioprotective Agents - Aghisna Binurillah Sulaeman; Dwi Anita Suryandari; Luluk Yunaini; Fadilah (Riviera Publishing, 2026)
Ionising radiation induces excessive oxidative stress and cellular damage, necessitating the discovery of effective radioprotective agents. The KEAP1–NRF2 pathway plays a central role in antioxidant defence, making KEAP1 inhibition a promising strategy for enhancing NRF2 activation. Centella asiatica contains diverse bioactive compounds with reported antioxidant and cytoprotective properties; yet their potential as direct KEAP1 inhibitors remains underexplored. This study aimed to evaluate the molecular interactions of Centella asiatica phytochemicals with KEAP1 using in silico approaches, in order to identify potential natural radioprotective candidates. Thirty-six bioactive compounds from Centella asiatica were subjected to molecular docking against the KEAP1 Kelch domain (PDB ID: 4L7B) using AutoDockTools 1.5.7. Ligand–protein interactions were visualised using LigPlot+ and PyMOL. Pharmacokinetic and toxicity profiles were predicted using DeepPK and admetSAR, including assessments of drug-likeness, intestinal absorption, CYP inhibition, and toxicity endpoints. Three compounds demonstrated strong binding affinities below –8 kcal/mol: acetylursolic acid (–8.88 kcal/mol), campesterol (–8.55 kcal/mol), and ursolic acid (–8.15 kcal/mol). All three interacted with the key KEAP1 residue Arg415, with additional interactions involving Ser363 (acetylursolic acid and ursolic acid) and Ser508 (campesterol). ADME–Tox analysis indicated favourable pharmacokinetic profiles, good intestinal absorption, non-mutagenic and non-carcinogenic predictions, and overall compliance with Lipinski's Rule of Five, notwithstanding a single LogP violation. Acetylursolic acid, campesterol, and ursolic acid exhibit strong binding to critical KEAP1 residues and demonstrate favourable pharmacokinetic and safety profiles, suggesting their potential as natural radioprotective agents through modulation of the KEAP1–NRF2 pathway. Further in vitro and in vivo studies are warranted to validate their radioprotective efficacy.